2018
DOI: 10.5433/1679-0359.2018v39n2p855
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Azospirillum brasilense with fungicide and insecticide and its effects on the physiological quality of wheat seeds

Abstract: Seed treatment is a practice that helps the initial establishment of the crop without the effects caused by pests and diseases. The association of diazotrophic bacteria with grasses has been used in the supply of nitrogen to plants; however, these microorganisms produce growth-promoting substances, which promote benefits in the growth and development of the crops. Thus, the objective of this study was to evaluate the compatibility of Azospirillum brasilense associated with the fungicide difenoconazole and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…There are few reports related to the effect of pesticides on Azospirillum spp. While some pesticides such as benomyl, thiamethoxam and tebuconazole seemed to be compatible with A. brasilense (Pereyra et al 2009;Elslahi et al 2014;Munareto et al 2018) pyraclostrobin + thiophanate-methyl, were not (Munareto et al 2018;Vogel and Fey 2019;Pereira et al 2020;Santos et al 2020aSantos et al , 2020b. The compatibility depends on the tested pesticide, the sensitivity of the biological inoculant and the applied inoculation methodology.…”
Section: Resultsmentioning
confidence: 95%
“…There are few reports related to the effect of pesticides on Azospirillum spp. While some pesticides such as benomyl, thiamethoxam and tebuconazole seemed to be compatible with A. brasilense (Pereyra et al 2009;Elslahi et al 2014;Munareto et al 2018) pyraclostrobin + thiophanate-methyl, were not (Munareto et al 2018;Vogel and Fey 2019;Pereira et al 2020;Santos et al 2020aSantos et al , 2020b. The compatibility depends on the tested pesticide, the sensitivity of the biological inoculant and the applied inoculation methodology.…”
Section: Resultsmentioning
confidence: 95%
“…Dartora et al [ 22 ] also found no effect of the fungicide fludioxonil-metalaxyl and of A. brasilense on the percentage of germination of maize seeds. Similarly, in wheat ( Triticum aestivum ), Muraneto et al [ 23 ] observed no differences in germination of seeds treated with fungicide, insecticide, and A. brasilense .…”
Section: Resultsmentioning
confidence: 99%
“…Fungicide application might have decreased the positive effects of T. harzianum inoculation and might even have affected plant responses to A. brasilense, B. subtilis, and P. fluorescens. A previous study showed that fungicides can have deleterious effects not only on fungi but also on bacteria and are not compatible with A. brasilense inoculated via seed treatment (Munareto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%